ANALYSIS OF LAND COVER CHANGES IN MANGROVE VEGETATION USING LANDSAT IMAGE DATA IN COASTAL, SUNGAI APIT DISTRICT, SIAK REGENCY, RIAU PROVINCE - Armanda Armanda; Mubarak Mubarak; Elizal Elizal (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
This research was conducted in March-April 2021 in the Coastal District of Sungai Apit, Siak Regency, Riau Province. The purpose of this study was to analyze changes in the land cover area of ​​mangrove vegetation and mangrove vegetation index in Sungai Apit District, Siak Regency, Riau Province. The method used in this study is a survey method with the interpretation of Landsat image data recorded in 2000, 2005, 2010, 2015, 2020. The results of the study obtained that mangrove forests with the highest area were in 2000 with an area of ​​mangrove vegetation reaching 7990,586 ha and there was a decline with the lowest number in 2015 with a vegetation area of ​​486,43 ha and in 2020 the mangrove vegetation area of ​​497,511 ha. Overall as much as 79% of the mangrove forest area has been damaged and changed its function within a period of 20 years. The NDVI value in Sungai Apit District is moderate with a value of 0,3-0,5, the category of meeting with a value of 0,5-0,6, and the very dense category of 0,6-0,8